Cooling-/water-responsive shape memory hybrids - Wang, Chang Chun (2013)
We report our experimental results of a hybrid which has both the cooling-responsive shape memory effect (SME) and water-responsive SME. The hybrid is designed based on the concept of shape memory hybrid (SMH), and is made of a plastic sponge (as elastic component) filled with Poloxamer 407 (P407) gel (as transition component). It is observed that the hybrid is able to recover its original shape upon immersing into 0 °C water in less than one minute (due to “melting” of P407 gel upon cooling), while upon immersing into 20 °C water, the recovery time is about one hour (due to dissolving of P407 gel in the water). Apparently, cooling for shape recovery is a complement to heating induced SME as in almost all traditional thermo-responsive shape memory materials. Mechanical properties of these samples are characterized by cyclic uniaxial compression test. Our experimental results reveal the compatibility and feasibility of P407 hybrid for biomedical applications inside human body. Potential biomedical applications are further discussed.